THE ROLE OF MATHEMATICAL GAMES IN ENHANCING LEARNERS’ MOTIVATION AND CONCEPTUAL UNDERSTANDING ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This study investigates the role of mathematical games in enhancing secondary school students’ motivation, engagement, and conceptual understanding of mathematics. The research emphasizes that traditional teaching methods often make mathematics seem abstract or disconnected from real-life experiences, leading to low student motivation and increased math anxiety. By incorporating game-based learning strategies, students are actively involved in exploring mathematical concepts through interactive, practical, and collaborative activities.